Peningkatan Kompensasi Terhadap Kinerja Pegawai pada Dinas Perhubungan Kota Jambi - Reni Devita (Universitas Batanghari, 2021)
The research method used in this research is descriptive and quantitative methods. The quantitative descriptive method aims to describe the nature of something that is ongoing at the time the research is conducted and examines the causes of a particular phenomenon. The data that will be collected will be analyzed, including secondary data analyzed descriptively, while primary data will be analyzed using analytical tools using SPSS program tools. Before the data is used in the SPSS program, the ordinal data is first used as an interval using the method of success interval (MSI) program. From the total population of 124 people studied, the sample became 55 Employees At The Transportation Office Jambi City The results of the study are as follows Compensation with an average score of 268.2 when viewed on the scale range, namely Very High, means that compensation at the Jambi City Transportation Service is in the Very High criteria. Performance with an average score of 265.3 when viewed on the scale range, namely Very High, meaning that the performance at the Jambi City Transportation Service is in the Very High criteria. Increasing compensation through stronger performance, increasing employee compensation will result in higher employee performance .The increase in compensation with the performance of the Jambi City Transportation Service employee has a coefficient of determination known from the value (R2) of 0.238 so that it can be interpreted that the increase given by the compensation variable on performance is positive. This condition means that this figure states that the compensation variable (X) is able to explain the employee performance variable (Y) at the Jambi City Transportation Service of 23.8%, whereas 76.2% is caused by other variables outside the variables studied. Compensation and Performance at the Jambi City Transportation Service is categorized as Very High. Based on the hypothesis test, it is known that there is a significant increase in the Jambi City Transportation Service Office, this is evidenced by the tcount 4.073 > ttable 1.67412.